2018
DOI: 10.1111/ijfs.14015
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of residual nutrients from agri‐food byproducts using a combination of solid‐state fermentation and insect rearing

Abstract: The present research develops an innovative nutrient recovery strategy for capturing of un-utilised nutrients from agri-food byproducts using a combination of solid state fermentation (SSF) and insect rearing. SSF of borage and flaxseed meals were performed using GRAS organisms to release indigenous nutrients and to produce additional nutrients. Proximate analysis of the SSF-meals showed increases in both lipid and protein contents. Black soldier fly larvae (BSFL) were then grown on these SSF-meals for 12 day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…We showed that BSFL can convert agricultural wastes into biomass with up to 95% recovery of organic matter using SSF [4,10]. Our previous research [4,10] suggests that FDK could be fed to BSFL to recover nutrients at a high rate with SSF treatment of feedstock. It is, however, unclear if the mycotoxins would be accumulated when BSFL are fed with FDK.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…We showed that BSFL can convert agricultural wastes into biomass with up to 95% recovery of organic matter using SSF [4,10]. Our previous research [4,10] suggests that FDK could be fed to BSFL to recover nutrients at a high rate with SSF treatment of feedstock. It is, however, unclear if the mycotoxins would be accumulated when BSFL are fed with FDK.…”
Section: Introductionmentioning
confidence: 83%
“…Larvae gained significantly more weight when fed with FDK fermented with Lp (58.4 ± 6.3 mg/larva). Kuttiyatveetil et al [4] assessed SSF borage meal and flaxseed meal as the feedstuffs and reported that the highest BSFL biomass was 87.4 mg/larva. The volume of BSFL increased from 66.8 ± 21.8 mm 3 to 352.7 ± 87.9 mm 3 when fed FDK fermented with Ao at day eight, and there were no significant differences among treatments.…”
Section: Growth Rate Of Bsflmentioning
confidence: 99%
See 3 more Smart Citations